Media True False Game Sebagai Alat Transformasi Pembelajaran Agama Islam Yang Efektif Di Era Digital - Auliya', Hilyatul; Hunaida, Wiwin Luqna; Muqit, Abd (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2024)
This study aims to explore the effectiveness of using True False Game media as a transformation tool in learning Islamic Religion in the digital era. The method used is library research by collecting data from various related literature sources. The results showed that True False Game can increase students' understanding and interest in learning in Islamic Religion subjects. This media allows interactive and fun learning, and encourages collaboration between students. The use of information and communication technology in the True False Game facilitates access to learning, allows direct evaluation, and supports the implementation of distance learning. Although effective, there are limitations relating to the dependence on technological infrastructure, which can hinder learning in the event of technical disruptions. The implication of this study is that the True False Game has great potential to be applied in learning Islamic Religion in the digital era, with adequate technological support and variations of other learning methods to ensure more comprehensive understanding.